Electrooxidation of biomass-derived 5-hydroxymethylfurfural into the 2,5-furandicarboxylic acid in microfluidic device with different path design - Unlu, Umran; Oruc, Muhammed Enes; Yucel, Ozgun (Elsevier Science Sa, 2025)
The polymer industry is constantly growing and becoming indispensable due to the ease of production and usage. However, the fact that many commercially produced polymers are derived from petroleum leads to a depletion of natural resources and significant environmental problems. As a result, there is a growing increase in the demand for environmentally friendly bio-based polymers as an alternative to conventional plastics. A bio-based polymer called polyethylene 2,5-furan dicarboxylate (PEF) is considered as a promising polymer due to its improved barrier and mechanical characteristics relative to polyethylene terephthalate (PET). The monomer of PEF is the 2,5-furan dicarboxylic acid (FDCA), which can be obtained by oxidation of bio-based 5-(hydroxymethyl) furfural (HMF). In this study, the electrochemical HMF oxidation to FDCA was performed, providing a green process compared to the conventional approach. At the same time, microfluidic electrochemical cells were designed because could be integrated into larger-scale systems with fewer steps. On the basis of this investigation, different designs were developed to investigate the effect of changes in flow rate (10-25 mL min-1) and diffusion path (straight, nodal, vertical and horizontal serpentine type path). The straight design (20 mL min-1) resulted in shorter process times and improved efficiency (99.3 %), compared to the performance of the batch system.
Keywords: 5-Hydroxymethylfurfural (HMF); FDCA; Microfluid; Electrooxidation